2014
DOI: 10.1063/1.4864657
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen diffusion and reactivity at low temperature on bare amorphous olivine-type silicate

Abstract: The mobility of O atoms at very low temperatures is not generally taken into account, despite O diffusion would add to a series of processes leading to the observed rich molecular diversity in space. We present a study of the mobility and reactivity of O atoms on an amorphous silicate surface. Our results are in the form of reflection absorption infrared spectroscopy and temperature-programmed desorption spectra of O2 and O3 produced via two pathways: O + O and O2 + O, investigated in a submonolayer regime and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 48 publications
3
32
1
Order By: Relevance
“…Recently Dulieu et al (2013) found that desorption probabilities of these reactions are very high, >90% and 60%, on a silicate substrate, while the probabilities are much lower on an ice substrate. Minissale & Dulieu (2014) found that the desorption probability of O + O → O 2 becomes smaller with the increasing ice coverage. Motivated by these experiments, we use the coverage dependent desorption probabilities for these two reactions and their deuterated analogues:…”
Section: Gas-grain Interaction and Surface Chemistrymentioning
confidence: 98%
“…Recently Dulieu et al (2013) found that desorption probabilities of these reactions are very high, >90% and 60%, on a silicate substrate, while the probabilities are much lower on an ice substrate. Minissale & Dulieu (2014) found that the desorption probability of O + O → O 2 becomes smaller with the increasing ice coverage. Motivated by these experiments, we use the coverage dependent desorption probabilities for these two reactions and their deuterated analogues:…”
Section: Gas-grain Interaction and Surface Chemistrymentioning
confidence: 98%
“…We have considered only thermal hopping, however, because most recent experiments do not indicate the existence of quantum mechanical tunneling for diffusive motion [36][37][38]. Minissale et al [39], on the other hand, have interpreted the rapid diffusion of oxygen on olivine at low temperatures as due to tunneling. In addition to the diffusive, or Langmuir-Hinshelwood, mechanism, surface reactions can occur via the Eley-Rideal mechanism, in which a gas-phase species collides with an adsorbate, leading to reaction.…”
Section: Grain Surface/mantle Reactionsmentioning
confidence: 99%
“…Recent experimental studies using FORMOLISM have highlighted the significance of the chemical desorption mechanism in the monolayer regime at low temperatures (Dulieu et al 2013;Minissale et al 2014;Noble et al 2011). It has been shown that up to 90% of molecules (on a graphite surface) formed by radical-molecule or radical-radical surface reactions sublimate from the surface after formation because of the inability of the surface to quench the energy released during the reaction.…”
Section: Proposed Reaction Mechanismmentioning
confidence: 99%